Isolation and antimicrobial susceptibility of Brachy -spira species from feces of layer chickens in Germany - Herbst, Werner; Willems, Hermann; Heuser, Jörg; Ewers, Christa (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2018)
Objective: Anaerobic spirochetes of the genus Brachyspira are important pathogens causing swine dysentery (Brachyspira [B.] hyodysenteriae) and porcine intestinal spirochetosis (B. pilosicoli, PIS). In addition, avian intestinal spirochetosis (AIS) is caused by B. pilosicoli, B. intermedia and B. alvinipulli. Despite the economic impact of AIS, the disease has not received appropriate attention in Germany. This study was aimed at identifying Brachyspira spp. in Germany and determining their antimicrobial susceptibility. Material and methods: From 2009 to 2013, a total of 71 fecal swabs were obtained from clinically healthy layer hens from eight different commercial flocks. Brachyspira spp. culture was performed in trypticase soybean agar added with 5% sheep blood. Species determination was conducted by PCRs targeting the NADH-gen and the 16S rDNA or by nox-gene sequencing. Antimicrobial susceptibility to macrolides, lincosamides and pleuromutilins was tested by a microdilution assay. Results:Brachyspira spp. were isolated from 40 (56.3%) swabs distributed over all eight flocks. In 26 cases, the following species were determined by PCR: B. pilosicoli (n = 16), B. intermedia (2), B. innocens (3), B. murdochii (1), mixtures of B. pilosicoli/B. intermedia (2), B. innocens/B. intermedia (1), B. innocens/B. murdochii (1). Remaining isolates were characterized by noxgene sequencing as B. “pulli” (n = 9), B. alvinipulli (3), B. intermedia (1) and as not identifiable (1). Antimicrobial susceptibility testing of 37 isolates revealed minimal inhibitory concentrations 90 (MIC90) of > 128 mg/l (tylosin), 64 mg/l (lincomycin), 8 mg/l (tiamulin) and 4 mg/l (valnemulin), respectively. Comparing to breakpoints applied to pigs, these values lie within the range of resistance. Conclusion The demonstration of different Brachyspira spp., particularly B. pilosicoli, intermedia and alvinipulli in commercial layers, indicates the need of further research to assess their potential role in causing AIS in German poultry flocks. The increased antimicrobial resistance of Brachyspira spp. isolates to tylosin and pleuromutilins is likely associated with extensive use of these drugs in poultry medicine.
Keywords: Poultry; spirochetes; occurrence; antimicrobial susceptibility